A preliminary investigation into the relationship between functional movement screen scores and athletic physical performance in female team sport athletes - Lockie, Robert G; Schultz, Adrian B; Callaghan, Samuel J; Jordan, Corrin A; Luczo, Tawni M; Jeffriess, Matthew D (Biology of Sport, 2015)
There is little research investigating relationships between the Functional Movement Screen (FMS) and athletic performance in female athletes. This study analyzed the relationships between FMS (deep squat; hurdle step [HS]; in-line lunge [ILL]; shoulder mobility; active straight-leg raise [ASLR]; trunk stability push-up; rotary stability) scores, and performance tests (bilateral and unilateral sit-and-reach [flexibility]; 20-m sprint [linear speed]; 505 with turns from each leg; modified T-test with movement to left and right [change-of-direction speed]; bilateral and unilateral vertical and standing broad jumps; lateral jumps [leg power]). Nine healthy female recreational team sport athletes (age = 22.67 ± 5.12 years; height = 1.66 ± 0.05 m; body mass = 64.22 ± 4.44 kilograms) were screened in the FMS and completed the afore-mentioned tests. Percentage between-leg differences in unilateral sit-and-reach, 505 turns and the jumps, and difference between the T-test conditions, were also calculated. Spearman’s correlations (p ≤ 0.05) examined relationships between the FMS and performance tests. Stepwise multiple regressions (p ≤ 0.05) were conducted for the performance tests to determine FMS predictors. Unilateral sit-and-reach positive correlated with the left-leg ASLR (r = 0.704-0.725). However, higher-scoring HS, ILL, and ASLR related to poorer 505 and T-test performance (r = 0.722-0.829). A higher-scored left-leg ASLR related to a poorer unilateral vertical and standing broad jump, which were the only significant relationships for jump performance. Predictive data tended to confirm the correlations. The results suggest limitations in using the FMS to identify movement deficiencies that could negatively impact athletic performance in female team sport athletes.